Female and Male Community-Level Empowerment: Capability Approach-Based Findings for Rural India - Melinda Schmidt; Harald Strotmann; Jürgen Volkert (The European Journal of Development Research, 2021)
This paper adds to the empirical research on empowerment drivers by analysing the empowerment of women and men at the community level. Using micro-data from four villages in rural Karnataka/India, our econometric estimations confirm several predictions of Sen's capability approach on potential determinants of empowerment. Education, decent employment, other-regarding agency goals, political networks, trust and fairness coincide with reported impact on community-level change. Gender-specific estimations demonstrate that most empirical drivers of empowerment are quite consistent for men and women in many respects. Some variables, however, notably higher education, correlate with community-level empowerment of men, but not of women, which emphasises different gender roles in rural Karnataka. These findings may help researchers and practitioners to further develop cause-related strategies to overcome major determinants of disempowerment in institutional village decision contexts in general as well as those which are gender-specific.
Keywords: 330; Community-level empowerment; Capability approach; Gender; Rural India; Human development; Agency